In vitro repair of DNA hairpins containing various numbers of CAG/CTG trinucleotide repeats - Zhang, Tianyi (2011)
Expansion of CAG/CTG trinucleotide repeats (TNRs) in humans is associated with a number of neurological and neurodegenerative disorders including Huntington’s disease. Increasing evidence suggests that formation of a stable DNA hairpin within CAG/CTG repeats during DNA metabolism leads to TNR instability. However, the molecular mechanism by which cells recognize and repair CAG/CTG hairpins is largely unknown. Recent studies have identified a novel DNA repair pathway specifically removing (CAG)(n)/(CTG)(n) hairpins, which is considered a major mechanism responsible for TNR instability. The hairpin repair (HPR) system targets the repeat tracts for incisions in the nicked strand in an error-free manner. To determine the substrate spectrum of the HPR system and its ability to process smaller hairpins, which may be the intermediates for CAG/CTG expansions, we constructed a series of CAG/CTG hairpin heteroduplexes containing different numbers of repeats (from 5 to 25) and examined their repair in human nuclear extracts. We show here that although repair efficiencies differ slightly among these substrates, removal of the individual hairpin structures all involve endonucleolytic incisions within the repeat tracts in the nicked DNA strand. Analysis of the repair intermediates defined specific incision sites for each substrate, which were all located within the repeat regions. Mismatch repair proteins are not required for, nor do they inhibit, the processing of smaller hairpin structures. These results suggest that the HPR system ensures CAG/CTG stability primarily by removing various sizes of (CAG)(n)/(CTG)(n) hairpin structures during DNA metabolism.